TEORI DILASI DALAM RUANG HILBERT DAN RUANG BANACH - Surachman, Annisanti; Rosjanuardi, Rizky; Yusnitha, Isnie (Jurnal EurekaMatika, 2016)
ABSTRAK. Pada artikel ini dibahas teori dilasi dengan ruang Hilbert sebagai ruang pokok dan kaitan antara beberapa teori dilasi yang terdiri dari pemetaan positif lengkap, kontraksi dan ukuran bernilai operator. Selain itu dibahas juga teori dilasi dengan ruang Hilbert sebagai ruang pokok.Kata Kunci: ukuran bernilai operator, pemetaan positif, Teorema Dilasi Naimark, ruang dilasi Hilbert dan ruang dilasi Banach.ABSTRACT. This paper tells about dilation theory with a Hilbert space as an underlying space andÂ  associations between some of dilation theory consist of completely positive maps, contraction and operator-valued measure. In addition also tells about dilation theory with a Banach space as an underlying space.Key words: operator-valued measure, positive maps, Naimarkâ€˜s Dilation Theorem, Hilbert dilation space, Banach dilation space.